Gold Mines: Towards Cancer Rescue - Beesetti Swarna Latha (Asian Pacific Journal of Cancer Biology, 2023)
Cancer remains as a major threat, despite of several pandemic outbreaks. The risk of every alternative disease or disorder increases with the initial incidence of cancer. Cancer treatment has radically changed a lot from conventional therapies like surgery and radiotherapy to targeted therapies like thermal ablation and gene therapy. The extension of applicative nanotechnology has become promising therapy in Cancer Diagnosis and treatment. The use of gold nanoparticles towards cancer therapy is discussed in this article.